Contemporary perspectives on play in early childhood education - Saracho, Olivia N.; Spodek, Bernard (Emerald Publishing Limited : Information Age Publishing, 2003)
This text looks at how the study of play has gained attention and concerns about play in young children have emerged. Ten chapters examine the understanding of play and its theories, play in school, pre-school and theories of pretence, mental representation and humour development.
Keywords: Play.; Early childhood education.; Education -- Schools -- Levels -- Early Childhood (incl. Preschool & Kindergarten); Early childhood care and education.; Pre-school and kindergarten.; elektronické knihy; electronic books